Effects of hot and cold meat deboning on the lipid oxidation changes and sensory properties of the traditional sausage: Petrovská klobasá - Šojić Branislav; Tomović Vladimir; Džinić Natalija; Tasić Tatjana; Škaljac Snežana; Ikonić Predrag; Jokanović Marija (Journal on Processing and Energy in Agriculture, 2016)
This paper investigates the lipid oxidation changes in the traditional dry fermented sausages Petrovská klobasá, from the area nearby the town of Bački Petrovac in the Autonomous Province of Vojvodina, made from hot (sausage A) and cold deboned meat (sausage B). Both groups of sausages (A and B) were produced according to the same recipe and subjected to drying and ripening processes under traditional conditions. The lipid oxidation changes were monitored via the acid number values and the TBARS test. During the storage period, the acid number significantly increased (p<0.05) in both groups of sausages. Lipid oxidation changes, expressed by the TBARS test, in the sausages B were significantly (p<0.05) lower in comparison with the sausages A. The sensory properties of odour and taste in the sausages B were significantly better (p<0.05) in comparison with the sausages A. The obtained results indicate that cold deboned meat causes lower lipid oxidation and better sensory stability of the traditional Petrovská klobasá sausage during the storage period.